2008
DOI: 10.2147/vhrm.s2175
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic implications of transesophageal echocardiography after transthoracic echocardiography on acute stroke patients

Abstract: Background:The role of transesophageal echocardiography (TEE) in the evaluation of acute stroke patients is still ill-defi ned. We conducted a prospective observational study to fi nd the prevalence of TEE fi ndings that indicate anticoagulation as benefi cial, in acute ischemic stroke patients without indication for anticoagulation based on clinical, electrocardiographic and transthoracic echocardiography (TTE) fi ndings. Methods: We prospectively studied all patients referred to our laboratory for TTE and TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Several studies demonstrated that TEE is superior to TTE for identification of a cardiac embolic source in patients with TIA or stroke (11,12). De Brujn et al (11), in patients with acute stroke, found a thrombus in 17% of the patients using TEE compared to 2% using TTE.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that TEE is superior to TTE for identification of a cardiac embolic source in patients with TIA or stroke (11,12). De Brujn et al (11), in patients with acute stroke, found a thrombus in 17% of the patients using TEE compared to 2% using TTE.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinicians prefer to perform TTE first, and if positive for cardioembolic stroke proceed with treatment, depending on the cause. However, if TTE is negative and TEE is not obtained, it is possible to fail to identify the source of cardiac embolism [15,16]. The risks of TEE include local irritation or injury to the oropharynx and esophagus; respiratory decompensation, especially in those with poor cardiopulmonary status (e.g., end-stage cardiopulmonary disease); increasing intracranial pressure, in patients who are at risk.…”
Section: Evaluation Of Patients At Risk For Cardioembolic Strokementioning
confidence: 99%
“…But even after comprehensive diagnostics, stroke etiology remains cryptogenic in 22-43% of patients (1)(2)(3). In such cases, transesophageal echocardiography (TEE) can be helpful to detect further cardiac or aortic sources of brain embolism (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%